2001
DOI: 10.4049/jimmunol.166.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD40 Antibody Induces Antitumor and Antimetastatic Effects: The Role of NK Cells

Abstract: We assessed the effect of the stimulatory anti-CD40 Ab on NK cell activation in vivo and the therapeutic potential of activated NK cells in tumor-bearing mice. Single-dose i.p. injection of the anti-CD40 Ab resulted in production of IL-12 and IFN-γ in vivo, followed by a dramatic increase in NK cell cytolytic activity in PBLs. NK cell activation by anti-CD40 Ab was also observed in CD40 ligand knockout mice. Because NK cells express CD40 ligand but not CD40, our results suggest that NK activation is mediated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 26 publications
7
89
1
Order By: Relevance
“…Macrophages (27,28), B cells (29), natural killer (NK) cells indirectly (30), and T cells (20) via dendritic cell activation have been suggested to play crucial roles in tumor eradication. We asked whether our local lowdose administration of anti-CD40 antibody would depend on the presence of CD8 þ T cells by using cell-depletion experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Macrophages (27,28), B cells (29), natural killer (NK) cells indirectly (30), and T cells (20) via dendritic cell activation have been suggested to play crucial roles in tumor eradication. We asked whether our local lowdose administration of anti-CD40 antibody would depend on the presence of CD8 þ T cells by using cell-depletion experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has shown that anti-CD40 mAb can promote therapeutic NK cell responses against murine tumors (32,33). Three experimental conditions were investigated to clarify the contribution of tumor cells and anti-CD40 to the NK cell response: in the first group, mice were given just the BCL 1 cells (5 ϫ 10 7 ) on day 0; in the second, mice received anti-CD40 alone on day 4; and in the third, mice received 5 ϫ 10 7 BCL 1 cells i.v.…”
Section: Anti-cd40 Mab Promotes An Nk Cell Responsementioning
confidence: 99%
“…However, we found no evidence that this played an important role in preventing lymphoma development or in curing the mice, because NK cell depletion using a polyclonal Ab (anti-ASGM1) did not block the efficacy of the CD40 mAb. Others have found CD40 stimulation with mAb or CD40L can up-regulate NK cell cytotoxic activity (32,33), and that, at least in some models, these can account for a major component of the therapeutic activity. The most likely explanation for such activity is through CD40-promoted production of Th1 cytokines such as IL-12 and IFN-␥.…”
Section: Figurementioning
confidence: 99%
“…Notably, this network of cell interactions has been shown to be involved in the regression of murine metastatic neuroblastoma (Turner et al, 2001). Thus, CD40 may represent a novel therapeutic, multifunctional target in NB because of its expression on both tumour cells and professional antigen-presenting cells.…”
Section: Discussionmentioning
confidence: 99%
“…Reverse transcription -polymerase chain reaction and sequencing RNA was extracted from freshly isolated or cultured cells using RNeasy Mini Kit from Qiagen (Qiagen GmbH, Hilden, Germany) and subjected to RT -PCR as reported (Turner et al, 2001). Primer sequences and profiles of amplification were the following: G3PDH 5 0 ACATCGCTCAGAACACCTATGG and 3 0 GGGTCTACATGG-CAACTGTGAG, CD45 5 0 CCTACAGACCCAGTTTCC and 3 0 GGC-AATCTTTTTCTGTCT, HLA-DRb 5 0 CTCCAGCATGGTGTGTCT-GA and 3 0 GGAGGTTGTGGTGCTGCAGG, CD40 5 0 CTGGGGCTG-CTTGCTGAC and 3 0 TCCTGGGGTTCCTGCTTG, CD80 5 0 GGTC-TTTCTCACTTCTGTTC and 3 0 CTTTCCCTTCTCAATCTCTC, CD86 5 0 ACACGGAGGCAGGGAACA and 3 0 GGAAAATGCTCT-TGCTTGGT, PD-1L 5 0 GGGAAATGGAGGATAAGA and 3 0 AG-GATGTGCCAGAGGTAG, B7H2 5 0 CCGAGCCCTGATGTCACC and 3 0 CCGCCACGACCACAAGCA, 4-1BBL 5 0 ACAAAGAGGACACGA-AGGAG and 3 0 GGAGGAGGCGGGTGGCAGGT, OX40L 5 0 TCAA-CATTAGCCTTCATTACC and 3 0 GAATCAGTTCTCCGCCATTCA.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%